Pendekatan Sejarah Terhadap Pentafsiran Al-Quran: Memahami Wahyu Dalam Konteks Peradaban Kontemporari: Historical Approach to the Interpretation of the Quran: Understanding Revelation in the Context of Contemporary Civilization - Lokman, Ainul Asyraf (Journal Al-Muqaddimah, 2025)
This article discusses in depth the historical approach as a critical methodology in contemporary Quranic interpretation. It traces the modern exegetical crisis arising from the pressures of colonialism, modernization, and global civilizational values, and further explains how the historical approach emerged as an epistemological response to make interpretation more dynamic, relevant, and grounded in socio-historical realities. The study emphasizes the shift from the dominance of Bayani epistemology to the integration of Burhani epistemology through the analysis of macro-historical contexts, Jahiliyyah culture, changes in social structures, and geopolitical relations in early Islam. The discussion also engages with key hermeneutical models, such as Fazlur Rahman’s Dual Movement, Nasr Hamid Abu Zayd’s historical dimension of the text, and Muhammad Shahrour’s Shari’ah Hududiyya, which offer methodological frameworks to distinguish between universal ethical principles and contextual laws. Through applications to issues such as gender, usury (riba), and public law reform in modern nation-states, the article demonstrates how the historical approach can restore the Quran’s function in social transformation. Although this approach faces theological polemics—particularly concerning the nature of Kalamullah, the theory of Naskh, and the origins of Western hermeneutics—the study argues that the historical approach can be critically integrated into the Islamic exegetical tradition without undermining the authority of revelation. The article further proposes a Bayani–Burhani methodological synthesis as a foundation for constructing a modern exegesis curriculum that is more responsive to the needs of contemporary society, in line with the objectives of Shariah (maqasid) and universal principles of justice.